Italienisches Capriccio - Kristl, Vlado (West Germany, 1969)
A trip-utopia of Kristl. As in his previous films, the filmmaker acts against the viewing habits of the viewer. He is provoked by unusual camera movements and cuts, and is aimed with its mounting against the conventional film syntax.
The film is contained with other pieces by Kristl: Kradja dragulja 1959, (9 min.), La peau de chagrin 1960, (10 min.), Don Kihot 1961, (11 min.), General i resni clovek 1962, (10 min.), Madeleine, Madeleine 1963, (10 min.), Der Damm 1964, (77 min.), Prometheus 1966, (10 min.), Film oder Macht 1970, (101 min.), Tigerkäfig 1971, (14 min.).
Languages: German, French, English. Options for the subtitles: German, French, English.